Identifying the Characters of Lion and Fox in the Aesop’s Fables using Transitivity System - Nabilla Alifiany Kusuma Putri; Deli Nirmala (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
This research investigates the Aesop Fables characters, the Lion and Fox, characterization analysis using transitivity system. This research aims to identify the characterization of Lion and Fox based on transitivity system using types of processes. This research using descriptive qualitative methods to describe the prominent clause that represents the Lion and Fox characterization. The non-participant observation methods were used to collect data and referential identity methods to analyze the data. The results show that material and verbal processes are discovered as the prominent process to represent the Lion and Fox's characterization. Through material and verbal processes, the Lion and Fox appeared in different characterizations. The Lion is discovered in manipulative, wise, powerful, and foolish characterizations. Meanwhile, the Fox found in cunning and talkative characterization. The finding also shows that the author constructed material and verbal processes because they are suitable for the children's limited knowledge. After all, material and verbal clause can be understood by the children easily.Keywords: transitivity system, characterization, narrative-stylistics, Aesop’s fables